RANCANGAN MEDIA HANDOUT BIOLOGI SMA KELAS XII PADA MATERI BIOTEKNOLOGI KONVENSIONAL - Timbir Manik; Imam Mahadi; Zulfarina Zulfarina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the potential of the handout design in class XII high school learning conventional biotechnology materials. This research was conducted at the Binawidya Campus, Riau University in September - November 2020. The design of this study used the ADDIE model, namely the analysis, design and development stages. Handout design in the form of an analysis of the potential development of high school learning media materials for Conventional Biotechnology Class XII semester II. This study uses an experimental method with a quantitative descriptive type of research. Based on the results of the potential analysis, it was found that sawdust had an influence on the growth of white oyster mushroom (Pleurotus ostreatus) and could be used as a handout design for conventional class XII biotechnology material in accordance with curriculum analysis, namely in KD 3.10 and 4.10.Key Words: Handout, Biotechnology material